Mapping signs and making them stick: discursive power and the semiotic construction of a 'world's leader'. Issue 5 (3rd September 2021) - Wong, Adrian
ABSTRACT: As multivalent concepts, projects and formations such as China's Belt and Road Initiative continue to cleave through new spaces, it is increasingly important to attend to the construction, framing, maintenance and dissemination of the sign systems that enable them. Whether or not these systems constitute forms of cultural imperialism, move across '-scapes, ' create 'frictions, ' or expand geo-political power; the discourses that globally extended actors mobilize will increasingly play the pivotal and contentious role of mapping and stabilizing meaning. This article explores this problematic by considering one actor, the Belt and Road Studies Network (BRSN); one space, its website, brsn.net; and the sign system these construct. The language and technological affordances of brsn.net are analyzed with respect to a selection of salient contextual aspects: the monumental revival of a new 'Silk Road', the propaganda work of the Chinese Communist Party (CCP) and the United Front Work Department (UFWD), and the expansion of think tanks in response to the continuous uncertainties of geo-political ecologies.